Effect of feeding live Lactobacillus acidophilus NCDC 15 and lactic fermented milk as probiotics on the performance of early weaned crossbred (Landrace × Desi) piglets - DHRUW, KALPANA; VERMA, A K; PATEL, B H M; AGARWAL, NEETA; SINGH, P (The Indian Journal of Animal Sciences, 2016)
The present study was undertaken to evaluate the effect of feeding live Lactobacillus acidophilus NCDC 15 and lactic fermented milk (LFM) as probiotics on the performance of early weaned crossbred (Landrace × Desi) piglets. Crossbred (Landrace × Desi) piglets (36) weaned at 28 days were assigned to treatments T1, T2 and T3 (12) following completely randomized block design. Piglets were fed concentrate mixture as per standards consisting of maize, soyabean, wheat bran and fish meal as a major ingredients. Piglets of T1 were fed basal diet without probiotics, while T2 and T3 were fed basal diet fermented with L. acidophilus NCDC 15 (200g/day/piglet, 5.8×107 cfu/g) and curd (200g/day/piglet, 6.7×107 cfu/g), respectively, for 120 days. Supplementation of probiotics (L. acidophilus NCDC 15 and LFM) to piglet diet improved total feed intake and the net body weight gain as compared to control group. The carcass parameters like carcass weight, dressing percentage, carcass length, back fat thickness and loin eye area was higher in L. acidophilus NCDC 15 and LFM supplemented groups as compared to control group where no probiotic was fed. Owing to the comparable affect of both the probiotics tested, it can be concluded that to improve the performance of the piglets, LFM (curd) can be used as probiotic.